Treatment of Complicated Femoral Fractures With External Skeletal Fixation Utilizing Bone Screws and Polymethylmethacrylate - Dew, T. L.; Kern, D. A.; Johnston, S. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Two femoral fractures initially treated using ASIF methods failed to proceed to union prior to implant loosening. The Inoue method of external skeletal fixation (ESF) employing AO/ASIF screws for fracture fragment fixation, a polymethylmethacrylate (PMMA) side bar and cancellous bone grafting was used. The dogs retained good limb function while the external fixators were in place. In case # 1 the fracture proceeded to union without further complications. The dog in case # 2 maintained good limb function, however fixation screw failure occurred prior to complete fracture healing.
Keywords: Inoue technique; external skeletal fixation; fracture non-union; polymethylmethacrylate